PENINGKATAN DAYA SAING KELOMPOK TANI MELALUI PEMANFAATAN TEKNOLOGI PERTANIAN - Shaleh, Khairul; Sukmawati, Fitri; Abas, Sa’adah; Mulyawan M.,H., R. Ferry; A, Dini Arwaty (LPPM Universitas Nusa Mandiri, 2024)
Indonesia is known as an agricultural region with a wide variety of agricultural and plantation commodities. Plantation commodities such as coffee plants are one of the superior products produced by farmers in Indonesia. Coffee plants grow in mountainous areas with relatively cold weather temperatures. Geographically, natural conditions support coffee plants to grow well even with limited technology. Community service activities aim to increase the competitiveness of coffee farmer groups through the application of technology. The community service activities were carried out in Mekarmanik Village, Cimenyan District, Bandung Regency, West Java Province. Service partner Tiwikrama Mukti Farmer Group is engaged in coffee plantations around Mekarmanik village. Coffee trees in this area are planted intercropped with rubber trees that grow on land owned by the PERHUTANI State-Owned Company. The method of implementing the service activities provides assistance with a set of grass cutting equipment and garden support equipment. This equipment can help farmers clean grass and weeds that often grow around the garden so that the growth of coffee plants can be better. In addition to providing agricultural equipment instruments, the service team provided simulations on the use of tools and counselling to farmer group partners regarding the market potential of coffee commodities. The results of community service activities in farmer groups after carrying out garden maintenance can increase coffee productivity. Coffee farmer groups also have a better understanding of coffee marketing circulation so that farmers obtain more optimal economic returns.